The Influence of Stigma on Community Attitudes Towards People with Mental Disorders in Gampong Krueng Juli, Kuala District, Bireuen Regency - Jihan Rabi'al; Khairiyatul Munawwarah; Meutia Chaizuran (Lembaga Pengembangan Kinerja Dosen, 2025)
Stigma is a negative label attached to an individual by society and influenced by the surrounding environment. In reality, individuals with mental disorders often experience greater stigma and discrimination from the community compared to those suffering from other medical illnesses. Ideally, the community should serve as a support system for people with mental disorders. This study aims to determine the influence of stigma on community attitudes toward individuals with mental disorders in Juli Seupeng Village, Juli Subdistrict, Bireuen Regency. This research is a quantitative study with a cross-sectional design. The sample consisted of 46 respondents, selected using purposive sampling. The study was conducted in Gampong Krueng July from August 10 to August 15. Data were analyzed using the Chi-square test. The univariate analysis showed that the majority of respondents had a high level of stigma (32 respondents or 69.6%), and most community attitudes were categorized as negative (38 respondents or 82.6%). The bivariate analysis revealed a p-value of 0.016, which is less than the significance level of 0.05 (ρ = 0.016 < α = 0.05), indicating a significant relationship between stigma and community attitudes toward individuals with mental disorders. Therefore, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It is recommended that communities change their mindset and perspectives, as negative attitudes can trigger relapses in people with mental disorders.